Does Lax Environmental Regulation Attract FDI When Accounting For "Third-Country" Effects? - Madina Kukenova; José-Antonio Monteiro (University of Neuchâtel, Institute of Economic Research (IRENE), 2008)
This paper investigates if differences in environmental regulations can influence FDI flows in a multi-country setting taking into account the so-called "third-country" effects. We examine bilateral FDI flows using a new extended OECD investment database which covers great number of host countries and a long sample period (1981-2005). The findings based on a spatial gravity-like model are largely plausible across specifications and confirm the existence of a negative relationship between FDI and environmental stringency, once we correct for endogeneity and spatial dependence. The evidence of a positive "third-country" effect for FDI suggests the prevalence of complex FDI from developed to developing countries. The spatial structure of the model allows also to underline the possible existence of competition in environmental standards between countries to attract FDI.
Keywords: F18; Q56; C31; 330; Complex FDI; Pollution Haven; Spatial Econometrics; System GMM